Perbedaan Kemampuan Komunikasi Matematis Sisswa Yang Belajar Menggunakan Model Pembelajaran Tipe Student Team Machievment Division Dan Tipe Numbered Head Together Di SMA PAB Helvetia - dwi andhika riandi; Zainal Azis (Lembaga Riset Mutiara Akbar, 2022)
This review aims to confirm that the numerical operational ability of students who study with the number head together type of learning model is superior to students who study with the group learning achievement division type of learning model in class X SMA PAB Helvetia. The population in this exploration is all class X IPA consisting of X IPA-1 as exploration class I who know how to use the number head together learning model and class X IPA-2 as the second trial class who are accustomed to using the student type learning model. team achievement division. The tools as pre-test and post-test are in the form of essays and are already valid by the mathematics teacher. PAB 6 Helvetia High School and 2 lecturers in the mathematics education department of FKIP UMSU. The normal value of the pretest class I trial was 42.90123457 and the normal value of the pretest. from the class II trial is 41.35802469 from the results of the investigation of pretest information which is usually scattered and homogeneous. Normal value. Final test. The trial class I was 87.030703704 and the posttest normal value for the exploration class II was 78.08641975. From the examination consequences, posttest information is usually adjusted and homogeneous. After showing speculation in the pretest, tcount (0.38861038) was obtained depending on the measures – tctable (- 2.21) < tmcount (0.38861038) < total (2.21). Furthermore, H0 is recognized so that there is no difference between the class trial and the class II trial. Speculation testing is directed at the posttest, obtained t count (2.2714553065) based on the standard t count (2.2714553065) < t table (2.21). So H0 is rejected and Ha is recognized so that it tends to reason that the numerical relational abilities of students who study with the number heado together learning model are superior to students who study with the student group achievement sharing learning model